Could a slow stable hybrid star explain the central compact object in HESS J1731-347? - Mariani, Mauro (2024)
We explore an alternative explanation for the low-mass ultracompact star in the supernova remnant HESS J1731-347 using a model-agnostic approach to construct hybrid equations of state. The hadronic part of the hybrid equation of state is constructed using a generalized piecewise polytropic scheme, while the quark phase is described by the generic constant speed of sound model. We assume an abrupt first-order hadron-quark phase transition with a slow conversion speed between phases. Our equations of state align with modern chiral effective field theory calculations near nuclear saturation density and are consistent with perturbative quantum chromodynamics calculations at high densities. Using this theoretical framework, we derive a wide range of hybrid equations of state capable of explaining the light compact object in HESS J1731-347 in a model-independent manner, without fine-tuning. These equations of state are also consistent with modern astronomical constraints from high-mass pulsar timing, NICER observations, and multimessenger astronomy involving gravitational waves. Our results support the hypothesis that the compact object in HESS J1731-347 could plausibly be a slow stable hybrid star.